2018
DOI: 10.1016/j.ehj.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase Glu 298 Asp (G894T) and Apolipoprotein E gene polymorphism as possible risk factors for coronary heart disease among Egyptians

Abstract: In Egypt, The prevalence of chronic heart disease (CHD) is 8.3%. It is the principal cause of death and is responsible for 22% of total mortality. The age-adjusted mortality rate is 174 per 100,000 of population. There are many studies on traditional risk factors and CHD in Egypt but the study of novel risk factors is deficient.ObjectivesThe aim of the present case control study was to investigate the relation between CHD susceptibility and Endothelial Nitric Oxide Synthase (eNOS) Glu 298 Asp (G894T) and Apoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In another study, no association was found between the 894G/T eNOS polymorphism and coronary artery disease in the northern Iranian population [60]. Accumulating evidence indicates that the Asp298Glu SNP of the eNOS gene is associated with coronary artery disease, ST-segment-elevation myocardial infarction, hypertension, coronary vasospasm, impaired coronary collateral development, impaired coronary blood flow, and obesity [14,[61][62][63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, no association was found between the 894G/T eNOS polymorphism and coronary artery disease in the northern Iranian population [60]. Accumulating evidence indicates that the Asp298Glu SNP of the eNOS gene is associated with coronary artery disease, ST-segment-elevation myocardial infarction, hypertension, coronary vasospasm, impaired coronary collateral development, impaired coronary blood flow, and obesity [14,[61][62][63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…1. The characteristics of the included studies [13][14][15][16][17][18][19][20][21][22][23][24], and the results of quality assessment based on NOS score are given in Table 1. The frequencies of APOE allele and distribution of genotypes are given in Table 2.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%